2018
DOI: 10.1021/acs.jpclett.8b00176
|View full text |Cite
|
Sign up to set email alerts
|

Probing Charge Transport through Peptide Bonds

Abstract: We measure the conductance of unmodified peptides at the single-molecule level using the scanning tunneling microscope-based break-junction method, utilizing the N-terminal amine group and the C-terminal carboxyl group as gold metal-binding linkers. Our conductance measurements of oligoglycine and oligoalanine backbones do not rely on peptide side-chain linkers. We compare our results with alkanes terminated asymmetrically with an amine group on one end and a carboxyl group on the other to show that peptide bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 42 publications
3
60
1
Order By: Relevance
“…Recently, Brisendine et al . studied the charge transport properties of unmodified peptides in aqueous solution, utilizing the carboxyl and amine group as gold metal‐binding linkers (as shown in Figure c) . They measured a serious of oligoglycine…”
Section: Charge Transport Mechanism Of Peptide Junctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Brisendine et al . studied the charge transport properties of unmodified peptides in aqueous solution, utilizing the carboxyl and amine group as gold metal‐binding linkers (as shown in Figure c) . They measured a serious of oligoglycine…”
Section: Charge Transport Mechanism Of Peptide Junctionsmentioning
confidence: 99%
“…Reproduced with permission from Brisendine et al . Copyright 2018, The Journal of Physical Chemistry Letters …”
Section: Charge Transport Mechanism Of Peptide Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,18 For this reason, the study of the conduction properties of individual peptides and polypeptides, which are their building blocks, is essential and sparking interest recently. 1,[19][20][21][22][23][24][25][26][27][28][29][30][31] It is well known that peptides can act as bridges for long-range electron transfer and that this process depends on details of the amino acid sequence as well as on their secondary structure. 32,33 The situation is not so clear in the case of electron transport through peptide-based molecular junctions, where it has been reported that homopeptide monolayers can be more conductive than, for instance, alkane chains.…”
Section: Introductionmentioning
confidence: 99%
“…29 However, it has also been shown that peptide bonds actually reduce the conductance of single-molecule junctions below those of saturated carbon chains. 31 This work is motivated by the experimental results of Ref. 34.…”
Section: Introductionmentioning
confidence: 99%